Supistuvat alueet ja kuntien käytännöt. Katsaus supistuviin alueisiin Suomessa - Huusari, Sanni; Inkinen, Tommi (Suomen Maantieteellinen Seura, 2026)
This study examines the phenomenon of shrinking regions in Finland, focusing on the strategies municipalities employ to adapt to population decline. The traditional approach to regional planning has emphasized growth, but many Finnish municipalities have experienced significant population loss due to low birth rates and outmigration. This paper explores the concept   of "smart adaptation," which involves sustainable planning and restructuring to maintain the quality of life despite demographic changes. Through a review of municipal strategies and expert interviews, the study identifies various adaptation methods, such as infrastructure reorganization, enhancing local cooperation, and improving residents' quality of life. The findings highlight the importance of context-specific solutions and the challenges municipalities face in implementing these strategies. The paper concludes that while smart adaptation is essential, it requires continuous adjustment and commitment from local governments.